Analisis Peran Roh Kudus Dalam Eksistensi Pelayanan Dan Pertumbuhan Gereja - Djone Georges Nicolas (Jayapangus Press, 2022)
Nowadays, churches are found that are led and managed like companies based on worldly principles, thus ignoring the important role of the Holy Spirit in them. Whereas the church is a fellowship of those who have received God's grace in faith in Christ. In order to reveal the light of God's Kingdom in the world, serve others, and grow with the aim of expanding God's Kingdom on earth. This paper aims to analyze the role of the Holy Spirit in the existence, ministry and growth of the Church by using descriptive qualitative methods related to the experience of the early church. Data collection was carried out through the Bible and various literature, journals, books, and interviews. As a result, the Holy Spirit acts as a church planter, empowers ministers to carry out church ministry duties, and drives church growth in all things. The conclusion is that the existence, ministry and growth of the church is the work of the Holy Spirit by deceiving believers for the fulfillment of God's work and plan for the world. so that the existence, ministry and growth of the church cannot be separated from the role of the Holy Spirit who works to realize the divine plan.